2015
DOI: 10.5301/hipint.5000207
|View full text |Cite
|
Sign up to set email alerts
|

The Regional Microvascular Density of the Gluteus Medius Tendon Determined by Immunohistochemistry with CD31 Staining: A Cadaveric Study

Abstract: The microvessel density was significantly lower in the length of the tendon (central portion) compared to the other 2 regions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…CTS002; Sigma-Aldrich; Merck KGaA). The sections were counterstained with hematoxylin for 30 sec at room temperature (17). Stained sections were observed using a light microscope (x200) and neovascularization was quantified using ImageJ software (v1.8.0; National Institutes of Health).…”
Section: Methodsmentioning
confidence: 99%
“…CTS002; Sigma-Aldrich; Merck KGaA). The sections were counterstained with hematoxylin for 30 sec at room temperature (17). Stained sections were observed using a light microscope (x200) and neovascularization was quantified using ImageJ software (v1.8.0; National Institutes of Health).…”
Section: Methodsmentioning
confidence: 99%
“…Immunohistochemistry studies utilising vessel markers have identified regions of hypo-vascularity in the central portion of the tendon. 63 This becomes more pronounced with age and may be key driver of tendinopathy. 64 A similar pattern has been observed in the rotator cuff, where a "critical zone" of decreased vascularity in the supraspinatus tendon is predisposed to injury and degeneration.…”
Section: Pathogenesismentioning
confidence: 99%